Cultural Distance and International Trade in Services: A Disaggregate View - Philipp Harms; Daria Shuvalova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We estimate the effect of “cultural distance” on bilateral trade in services. Our measure of cultural distance is based on scores that reflect individuals' attitudes towards hierarchies, initiative, competition, uncertainty etc. Controlling for other standard ingredients of gravity equations, we show that cultural distance has a negative effect on services trade. However, the strength and sign of this effect differs across various aspects of cultural distance and for various types of services.
Keywords: F14; 330